ANALISIS MANAJEMEN BISNIS SYARIAH DALAM STRATEGI PEMASARAN PRODUK PERSEROAN TERBATAS KANDAKAWANA SAKTI KABUPATEN BOGOR - Anggi Muhamad Fahrudin; Rully Trihantana; Bayu Purnama Putra (SAHID BUSINESS JOURNAL, 2022)
Analysis of sharia business management can be carried out on the marketing strategy of a company or limited liability company in order to continue to increase its sales turnover. Marketing strategy is closely related to the marketing mix of a company or limited liability company which generally uses the theory of Product, Place, Price, and Promotion, but it cannot be separated from the principles of sharia business management. In sharia business management, basically according to the rules of muamalah, everything is legal, unless there are arguments that forbid it. The most important thing in the application of sharia business management to marketing strategies is to prohibit all forms of false transactions that will cause harm to others such as usury, fraud, gharar. The purpose of this study is to determine and analyze the sharia business management of the marketing strategy carried out by the Kandakawana Sakti Company or Limited Liability Company. This analysis also uses the SWOT analysis technique as part of the research method with a qualitative approach. SWOT analysis to find out what strengths, weaknesses, opportunities, and threats from the marketing strategy need to be carried out by the company or limited liability company in the future. The results of the research as shown in the Cartesian diagram show that the company or limited liability company is in quadrant I, which is aggressive with the implementation of the Growth Oriented Strategy, which means a favorable situation for the company or limited liability company. With the strength it has, it can take advantage of the opportunities that exist. Based on the research that has been done, there are several suggestions for the Kandakawana Sakti Limited Liability Company to implement innovation and process and marketing variations, so that they can attract consumers and add more partners who are able to increase sales turnover. For further research, the results of this study can be continued to develop marketing strategies.